DIRECTING TECHNIQUES FEATURE TELEVISION “SETENGAH HATI KURANGI PLASTIK” - Pratami, Arvi Ristiani (Jurnal Visi Komunikasi, 2022)
Indonesia is the second largest contributor to plastic waste in the world. Not only pollutes the environment, plastic waste also causes animals to die. Some people are starting to become aware of the dangers of plastic waste. However, that is only a small part. This final project aims to make people aware that plastic waste is a problem that must be solved together. The theory used as the basis for this final project is hypodermic needle theory which has the principle of stimulus-response principle where the effect is a reaction to a particular stimulus. This theory considers that the mass media coverage is like a drug that is injected into the blood vessels of the audience, which then the audience will react as expected. This applicative final project design concept is made in a television news feature program format entitled Half a Heart Reduce Plastic. The format of the media used is digital 16: 9. This work is intended for all people. Based on the results of the production of plastic waste problems can be resolved if the government draws up regulations that regulate production to the recycling of plastic waste, the community must also contribute by reducing the use of plastic, and producers are asked to process their own plastic waste from production.